Автоматизированные системы управления предприятиями учебник - Четвериков В. Н. Владимир Николаевич; Воробьев Г. Н. Герман Николаевич; Казаков Г. Н. Геннадий Иванович; Кононыхин В. Н. Владимир Николаевич; Меньков А. В. Александр Викторович (Москва, Высшая школа, 1979)
Авт. указ. на обороте тит. л.